Multidrug resistance in Pseudomonas aeruginosa isolated from nosocomial respiratory and urinary infections in Aleppo, Syria - Maysa Mahfoud; Mona Al Najjar; Abdul Rezzak Hamzeh (Journal of Infection in Developing Countries)
Introduction: Pseudomonas aeruginosa represents a serious clinical challenge due to its frequent involvement in nosocomial infections and its tendency towards multidrug resistance. Methodology: This study uncovered antibiotic susceptibility patterns in 177 isolates from inpatients in three key hospitals in Aleppo, the largest city in Syria. Results: Exceptionally low susceptibility to most routinely used antibiotics was uncovered; resistance to ciprofloxacin and gentamicin was 64.9% and 70.3%, respectively. Contrarily, susceptibility to colistin was the highest (89.1%). Conclusions: Multidrug resistance was rife, found at a rate of 53.67% among studied P. aeruginosa isolates.